(untitled) (Journal of the College of Basic Education, 2022)
There is no doubt that access to achieving the best results is through following accurate and objective scientific methods in a sound and planned manner, including the use of educational methods that take into account individual differences among learners, which helps to highlight some of their abilities and personal and dynamic characteristics, and that the educator has an important impact on understanding the personality of learners To create appropriate educational conditions and deliver information to the learners, so choosing the best educational methods that achieve goals, taking into account individual differences, is one of the important foundations that must be taken into account in the educational process.